Gender heterogeneity in the boardroom and corporate sustainability performance of quoted manufacturing firms in Nigeria - Chinedu Francis Egbunike; Ikponmwosa Michael Igbinovia; Chinyere Patricia Oranefo; Agbonrha-Oghoye Imas Iyoha (AJAR (Asian Journal of Accounting Research), 2023)
Purpose – Prior studies have shown that heterogeneity plays a crucial role in addressing soft issues linked to a firm’s corporate social responsibility stance. The purpose of this paper is to extend the prior literature on the effect of gender heterogeneity on environmental, social and economic performance dimensions, specifically, whether the female boardroom presence weakens or strengthens the performance along the three dimensions, commonly referred to as the corporate sustainability. Design/methodology/approach – The study from a positivist philosophy adopts a quantitative approach, and the final sample consisted of forty-six companies listed on the Nigerian Stock Exchange for the year 2011–2018. The final sample was a balanced panel of 344 firm years. The dependent variables were return on assets (ROA), environmental performance (ENV) and donations made for social causes (SOP). The ENV was measured using a content scoring system, with range of 1 to 5. The data were analysed using the fixed effects and GLM regression models. To further address the issue of endogeneity, a two-stage least squares regression was conducted. Findings – The findings show a positive relationship between gender heterogeneity and ROA, which was also confirmed for the environmental performance index. However, the sign reversed in the SOP model and showed a negative relationship between gender heterogeneity and donations, the proxy for SOP. The results are in tandem with the stakeholder axioms that argue that commitment to other stakeholder groups strengthens firm performance in the long run. Research limitations/implications – An implication of this study is the fact that information availability has been rapidly escalating in the country, leading to rising social movements and civic unrest; therefore, corporations that face negative castigations may pay the huge price of product boycott and loss of market value. Originality/value – The findings of this study provide additional insight into the influence of female boardroom presence on the environmental, social and economic performance of firms. The findings suggest the relevance of the resource dependence theory, especially from a developing country context, to ensure an improved corporate governance structure in Nigerian manufacturing firms.